Predictions of produced water quality and quantity for spatially-distributed wells in Niobrara formation - Mingazetdinov, Ildus F., author; Carlson, Kenneth, advisor; Sutton, Sally, committee member; Catton, Kimberly, committee member (Colorado State University. Libraries, 2012)
Two main problems facing the oil and gas industry are the availability of water for well construction and disposal of the produced water. Produced water is typically only treated for a limited number of constituents, and common disposal options have been deep well injection, evaporation or discharge to wastewater treatment plants. However, because of factors such as regulations, local water shortage, and bans on disposal via deep well injection, the future will require much of the produced water be treated and eventually recycled and reused for future field development or other beneficial uses. Multiple cost effective produced water treatment methods have been developed but limited research has been done to understand produced water production volumes and quality from oil and gas fields. Accurate predictions of produced water volumes and quality over a period of time can be used to optimize design and siting of water handling and treatment facilities in a spatially heterogeneous shale oil and gas field. The information can also be used to model availability of water resources and plan long term recycling strategies for augmenting regional surface water supplies. This study describes protocols to estimate and predict produced water quantity and quality from shale gas wells and applies these to a case study of Noble Energy Inc. wells in Yuma County, CO. Three different protocols of water production prediction were developed based on temporal and spatial variations of water quantity. Dissolution kinetics and geospatial data were used to develop a water quality prediction framework. A Microsoft Excel based tool, which uses a combination of water quantity and quality protocols, was developed to predict water production and total dissolved solids (TDS) from Noble Energy Inc. wells in Yuma County for different field development scenarios. A framework for interactive web based applications based on developed protocols is also provided. This study also provides a framework for development of GIS based web applications, which can provide an analysis platform for producers and consulting firms to predict water production and/or water quality, optimize location of treatment facilities, truck routings and help make other decisions related to water management. The study showed that using decline models to predict water production from shale gas fields will provide better long term predictions rather than using historical production average values. The case study and scenarios used for Noble Energy wells in Yuma County demonstrate that these prediction methods can be used in any other shale gas field by altering decline models and coefficients.
Keywords: produced water prediction; produced water volumes; produced water quality prediction